The Effect of Nutrition Counseling Using "My Plate Media Content" on Nutritional Knowledge Levels of Mothers of Toddlers Participating in Nutrition Classes - Abdi, Lalu Khairul; Amalia, Yanti; Darni, Joyeti; Suhaema, Suhaema (Jurnal Kesehatan Prima, 2024)
The level of knowledge or lifestyle can lead to a pattern of multiple nutritional problems. Indonesia currently has a triple burden of nutrition problems, namely stunting, wasting and underweight as well as micronutrient deficiencies such as anemia. Data from the EPPBGM results of the Madapangga Health Center in August 2022 there were 2058 toddler targets, from these data showed 227 people (11.03%) targets experiencing underweigh, 157 people (7.63%) stunting, and 233 people (11.32%) wasting. The purpose of this study was to determine the effect of nutrition counseling using media contents of my plate on the level of nutritional knowledge of mothers of toddlers participating in nutrition classes.The research method used is a quasi experiment design with a Non Equivalent Control Group Design. Activities were carried out in February-March 2023, for 3 weeks with 3 meetings in each group with 60 research subjects consisting of 30 people in the treatment group and 30 people in the control group. The analysis used in this study was the Independent t test on 60 respondents in two classes, to determine the effect before and after providing nutritional counseling. The intervention provided was in the form of providing counseling with the "My Plate Contents" media for the treatment group and providing counseling without the "My Plate Contents" media for the control group. Data collection used questionnaires to measure the level of knowledge.Based on the results of the study, the level of knowledge of mothers of toddlers increased after being given nutritional counseling using media contents of my plate obtained p < 0.05, namely 0.026 < 0.05. Based on the Independent t Test test, it was concluded that there was an influence before and after counseling on the knowledge of mothers under five. So that the conclusion is that there is a significant effect of nutrition counseling using "Media Isi Piringku" on the level of nutritional knowledge of mothers participating in nutrition classes in the work area of the Madapangga Health Center, Bima Regency.